On the Gradience of English Size Nouns: frequency, productivity, and expansion - Herda, Damian (Baltic Journal of English Language, Literature and Culture, 2022)
The synchronic degrees of grammaticalization of size nouns are traditionally measured based on proportionate frequencies of their quantificational attestations in corpus samples. However, grammaticalization, in general, is associated not only with an increased frequency of grammaticalized uses but also with a rise in productivity and distributional expansion. Thus, drawing on corpus data encompassing selected English size nouns which originally individuate concrete inanimate nominals, this paper investigates the relationship between the three aforementioned parameters. Productivity is operationalized as the arithmetic mean of two measures, namely type-token ratio (TTR) and hapax-token ratio (HTR), i.e. the number of, respectively, types of quantified collocates and hapax legomena N2s divided by the number of all quantifier tokens of each expression, while host-class expansion is construed as the proportion of animate and abstract collocates among the respective items’ quantifier uses. Contrary to expectations, the results reveal only a weak positive correlation between the elements’ frequency values and their levels of productivity, and the same holds for the relation between frequency and distributional extension. Also surprising is the moderate negative correlation observed between productivity and expansion, which can nevertheless be elucidated in terms of a high type frequency of semantically general animate and abstract N2-collocates of the most distributionally extended expressions.